A QUALITATIVE STUDY OF THE EXPERIENCE OF FEMALE DIABETES MELLITUS TYPE II WITH SEXUAL DIFFUSION - Sulastri, Rafika; Permana, Imam (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
The sexuality of women with diabetes mellitus has not received much attention from the health team because patients rarely complain about it. This is related to cultural factors that are considered taboo. Research related to a sexual dysfunction that occurs in women with DM is relatively low. This study aims to explore the experiences of female patients with  type II DM who experience sexual dysfunction. This study used a phenomenological qualitative design, 8 participants were women with type II DM. The results of this study showed the impact of sexual dysfunction greatly affected the quality of life of the participants, where participants experienced disturbances when having sexual intercourse namely decreased desire, and pain during intercourse, creating feelings of guilt then resulting in disharmony in the household which can trigger psychological problems namely feeling low self-esteem, disturbed body image, and depression. The role of the health team is necessary to carry out early screening and sexual assessment in patients with DM to find out whether there is a sexual dysfunction disorder. Sexologist is also needed in dealing with patients who experience sexual dysfunction due to type II DM so they can arrange appropriate interventions.Keywords: Experience, DM type II, Female Sexual Dysfunction